How do you solve -2p - 2= - 5- 2( p + 5)?

1 Answer
Sep 15, 2017

Refer to explanation

Explanation:

-2p-2=-5-2(p+5)

This is the equation ^^

Let's focus on the right side
-2(p+5)
First we distribute the brackets/parentheses using this
a(b+c)=ab+ac
So using this it would be
-2*p-2*5
Then we take 5xx2=10
So -2p-10.

Now we will add in the -5.
-5-2p-10 We will put the variable p to the left and the numbers to the right.

-2p-5-10 which is equal to -2p-15 Then now you take the equation on the left. (-2p-2) From this, it means that

-2p-2=-2p-15 And this does not make sense.

So, this equation is unsolvable.